Agomir of miRNA-30d – a potential new therapeutic target for prevention of ischemic cardiomyopathy after myocardial infarction?. (3rd October 2022) - Boxhammer, E; Wernly, B; Kiss, A; Paar, V; Aigner, A; Podesser, B K; Zauner, R; Wally, V; Koeller, C; Hackl, M; Hoppe, U C; Lichtenauer, M
Abstract: Background: MicroRNA (miR)-30d is not only a valuable biomarker for assessing the extent of cardiac remodeling after myocardial infarction (MI), but also an important predictor of clinical outcome in heart failure. Overexpression of miRNA-30d appears to have a cardioprotective effect by preventing cardiomyocyte apoptosis as well as averting cardiac fibroblast proliferation via multiple molecular pathways. The aim of the present in vivo and in vitro study was to demonstrate whether an miR-30d can be a potential therapeutic target to reduce the risk of ischemic cardiomyopathy (iCMP) after MI. Methods: First of all, miRNA profiling was performed by next generation sequencing (NGS) to assess differences in miRNA expression in ischemic vs. healthy myocardium in a rat model of MI using coronary artery ligation (ischemia/reperfusion injury, IR). MiR-30d was selected as the most promising target as it was significantly downregulated in ischemic myocardium and can be upregulated by cardioprotective agents. Therefore, an agomir of miR-30d was administered in the respective treatment group intraperitoneally, whereas non-functional, scrambled miRNA was administered in the control group. To analyze the ratio between phosphorylated p53 (pp53) and total p53, apoptosis was evaluated in human cardiomyocytes using a p53 and pp53 ELISA kit. To gain indirect insight into infarct healing, scratch assays were used to obtain information on cell migration in human umbilical vein endothelial cells (HUVEC) in vitro. Six weeks after the in vivo induction of acute MI/IR with consequential iCMP in a rat model, the extent of MI was evaluated by planimetry. Results: The majority of miRNAs studied here showed significant up-regulation in the MI-induced heart tissue in comparison to the sham operated controls. In contrast, miRNA-30d was highly significantly reduced (p<0.001). Based on these investigations and the already repeatedly documented cardioprotective effect of miR-30d overexpression, an agomir was selected as a potential therapy target. Human cardiomyocytes under the influence of an agomir of miR-30d showed a decreased pp53/total p53 ratio (0.66±0.09 vs. 0.81±0.19) and thus a distinct tendency (p=0.055) for a reduction in apoptotic rate compared to the control group. In HUVECs, gap closure was significantly faster in the agomir treated cells 20h and 26h post-scratching (19.1% more than scrambled control after 20h; p=0.0028 and 18.7% more than scrambled control after 26h; p=0.0081). In the in vivo model, infarct size of left ventricle was significantly reduced by using the agomir (7.43±4.13% vs. 12.76±4.76%; p=0.0172). Conclusion: Using an agomir of miR-30d underlines the cardioprotective effects of miR-30d in MIR/IR and could reduce the risk for iCMP development. Further investigations regarding its therapeutic potential in the human should be considered, as microRNA treatments are gaining more and more clinical applicability today. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Paracelsus Medical University, PMU-FFF